Abortive and teratogenic effect of Acanthospermum hispidum DC. and Cajanus cajan (L.) Millps. in pregnant rats - Lemonica, I. P.; Alvarenga, CMD (Elsevier B.V., 1994)
Extracts of Acanthospermum hispidum and Cajanus cajan have been used by Brazilian people in an attempt to produce abortion. In order to evaluate the possible abortive and/or teratogenic effect of these plant extracts, female Wistar rats were treated with the aqueous extract (infusion, proportion C. cajan and A. hispidum 1:1.3). Doses of 0, 150, 300 and 600 mg/kg were daily administered by gavage during the organogenic period. The animals were sacrificed at term. There was no significant change in the mean weight of the fetuses, and no change in the percentage of post implantation loss in the treated groups. However, there was an increase in the number of external malformations, and this was related to dose. No internal malformations were observed in fetuses at term, but there was a significant incidence of fetuses with visceral anomalies. The tendency of the pregnancy to continue or terminate did not change with the treatment.
Keywords: EMBRYOTOXICITY; ABORTIVE PLANT EFFECTS; TERATOGENICITY